2006
DOI: 10.1177/0115426506021004351
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Chain Fatty Acids: Ready for Prime Time?

Abstract: The concept of colonic health has become a major target for the development of functional foods such as probiotics, prebiotics, and synbiotics. These bioactive agents have a profound effect on the composition of the microflora, as well as on the physiology of the colon, and display distinct health benefits. Dietary carbohydrates escaping digestion/absorption in the small bowel and prebiotics undergo fermentation in the colon and give rise to short-chain fatty acids (SCFA). As the main anions of the colon and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
277
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(290 citation statements)
references
References 131 publications
(156 reference statements)
5
277
0
8
Order By: Relevance
“…This coincides with the fact that most of the monocarboxylates produced by bacterial fermentation, such as butyrate and propionate, occur in the large intestine. Furthermore, it is reported that butyrate forms the main nutrition for the colon epithelium and is necessary for differentiation of colonocytes (42,43). Interestingly, we found that SLC5A8 has a strong prevalence to transport lactate but does not contribute significantly to the butyrate or propionate uptake of the colon at physiological conditions.…”
Section: Discussionmentioning
confidence: 56%
“…This coincides with the fact that most of the monocarboxylates produced by bacterial fermentation, such as butyrate and propionate, occur in the large intestine. Furthermore, it is reported that butyrate forms the main nutrition for the colon epithelium and is necessary for differentiation of colonocytes (42,43). Interestingly, we found that SLC5A8 has a strong prevalence to transport lactate but does not contribute significantly to the butyrate or propionate uptake of the colon at physiological conditions.…”
Section: Discussionmentioning
confidence: 56%
“…SCFAs, which are produced from fermentation of dietary fibers caused by anaerobic bacteria in the intestinal lumen, represent 90% of all the energy supplies used by the epithelial cells of the colon mucosa 23 . SCFAs modulate both cell proliferation and local immunity and they have an important role in relation to the integrity of the colon epithelium 24,25 . Reductions in the supply of SCFAs, as occurs during intestinal diversion operations, are accompanied by morphological and functional changes, thereby causing reductions in protein synthesis capacity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Kwas masłowy w jelicie grubym powstaje głównie w wyniku rozkładu pentoz [3], a kwas glukonowy może być prebiotykiem wybiórczo stymulującym powstawanie maślanu. Najbogatszymi źródłami kwasu masłowego w jelicie grubym są: oporna skrobia, owies i otręby pszenne [3].…”
Section: Wytwarzanie Krótkołańcuchowych Kwasów Tłuszczowych I Kwasu Munclassified
“…Najbogatszymi źródłami kwasu masłowego w jelicie grubym są: oporna skrobia, owies i otręby pszenne [3]. Oporna skrobia znajduje się w takich pokarmach, jak: częściowo zmielone ziarna zbóż i nasiona, surowe ziemniaki, zielone banany, warzywa oraz skrobia z dużą zawartością amylozy.…”
Section: Wytwarzanie Krótkołańcuchowych Kwasów Tłuszczowych I Kwasu Munclassified
See 1 more Smart Citation